Does Low Body Mass Index Predict Mortality in Asian Hospitalized Patients?. Issue 4 (25th September 2019) - Xue, Zhigang; Yu, Jianchun; Higashikuchi, Takashi; Compher, Charlene
Abstract: Background: Studies on malnutrition suggest low body mass index (BMI) may be associated with poor clinical outcomes. We investigated published data to identify whether low BMI could predict short‐term and long‐term clinical outcomes in Asian hospitalized patients. Methods: A search was conducted in the PubMed database including terms "body mass index" or "BMI" or "malnutrition" or "undernutrition" AND "Asia" or "Asian" AND "outcome" or "complication" or "mortality" or "survival" or "ICU" for publications in English in the past 10 years. Papers with data and clinical outcomes from Asian hospitalized patients with BMI <18.5 kg/m 2 and sample size >50 were included. Forest plots were constructed to determine the odds of hospital complications, hospital mortality, intensive care unit (ICU) mortality, and 5‐year mortality in patients with BMI <18.5 kg/m 2 vs BMI ≥18.5 kg/m 2 . Results: Twenty‐three studies were included, 16 of which were analyzed for the association between low BMI and clinical outcomes. The prevalence of BMI <18.5 kg/m 2 varied from 3% to 48% in different disease settings and Asian areas. Patients with BMI <18.5 kg/m 2 had significantly higher ICU mortality (odds ratio [OR], 1.92; 95% CI, 1.84–2.01), higher hospital mortality (OR, 2.48; 95% CI, 2.42–2.55), and higher 5‐year mortality (OR, 2.74; 95% CI, 2.08–3.63). Complications during hospital stay were significantly higher in patients with BMI <18.5 kg/m 2 (OR, 1.99; 95% CI, 1.65–2.40). Conclusions: Low BMI defined as <18.5 kg/m 2 may predict worse short‐term and longer‐term outcomes in Asian hospitalized patients.